2011
DOI: 10.1634/theoncologist.2010-0127
|View full text |Cite
|
Sign up to set email alerts
|

DNA Mismatch Repair Gene Polymorphisms Affect Survival in Pancreatic Cancer

Abstract: Purpose. DNA mismatch repair (MMR) maintains genomic stability and mediates cellular response to DNA damage. We aim to demonstrate whether MMR genetic variants affect overall survival (OS) in pancreatic cancer.Materials and Methods. Using the Sequenom method in genomic DNA, we retrospectively genotyped 102 single-nucleotide polymorphisms (SNPs) of 13 MMR genes from 706 patients with pancreatic adenocarcinoma seen at The University of Texas MD Anderson Cancer Center. Association between genotype and OS was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…This result does little to resolve the ambiguity in the literature surrounding the prognosis of mismatch repairdeficient pancreatic ductal adenocarcinomas, with select reports showing no prognostic value, 19,22 and other studies suggesting mismatch repair status is a prognostic marker in pancreatic ductal adenocarcinoma. 18,20,21 The incongruent nature of the studies mentioned above may be explained by the relatively small sample size used and the heterogeneity in treatments applied across studies. Of note, this study and Ottenhoffe et al 19 used immunohistochemistry on tissue microarray to assess mismatch repair status, yet significant prognostic value has only previously been correlated to mismatch repair status as defined at the DNA level by microsatellite instability assessment 18,20 and other methods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result does little to resolve the ambiguity in the literature surrounding the prognosis of mismatch repairdeficient pancreatic ductal adenocarcinomas, with select reports showing no prognostic value, 19,22 and other studies suggesting mismatch repair status is a prognostic marker in pancreatic ductal adenocarcinoma. 18,20,21 The incongruent nature of the studies mentioned above may be explained by the relatively small sample size used and the heterogeneity in treatments applied across studies. Of note, this study and Ottenhoffe et al 19 used immunohistochemistry on tissue microarray to assess mismatch repair status, yet significant prognostic value has only previously been correlated to mismatch repair status as defined at the DNA level by microsatellite instability assessment 18,20 and other methods.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, this study and Ottenhoffe et al 19 used immunohistochemistry on tissue microarray to assess mismatch repair status, yet significant prognostic value has only previously been correlated to mismatch repair status as defined at the DNA level by microsatellite instability assessment 18,20 and other methods. 21 The cohort used in this study is uniquely positioned to address treatment efficacy because of the large number of untreated cases, which serve as a control group. Unlike in mismatch repair-proficient pancreatic ductal adenocarcinomas, none of the clinico-pathologic covariates examined demonstrated independent prognostic significance in mismatch repair-deficient group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that DNA repair gene polymorphisms contribute to the development of pancreatic cancer (Li et al, 2009;Dong et al, 2011Dong et al, , 2012. There are several types of DNA damge, such as double-strand breaks (DSBs).…”
Section: Introductionmentioning
confidence: 99%